Synthesis of New Î²-adrenoceptor Blocking Agent Including 1,3,4 Thiadiazole with Expected Adrenoceptor Blocking Activity - Salah H. Zain Al-Abdeen; Ahlam J. Qasir (College of Pharmacy University of Baghdad, 2017)
Î²-Adrenergic blocking agents, mostly comprising of Î²-amino alcohols, are of pharmaceutical significance and have received major attention due to their utility in the management of cardiovascular disorders including hypertension, angina pectoris, cardiac arrhythmias and other disorders related to the sympathetic nervous system. Most compounds available for clinical use belong to the aryloxypropanolamine series, which is considered the second generation of Î²-blocking agents. The present study includes the synthesis of compounds with an N-substituted oxypropanolamine moiety attached to the 1, 3, 4-thiadiazole derivatives. According to this information, eight compounds were synthesized and characterized by IR spectra and elemental microanalysis that confirmed the structural formula of these compounds. Keywords: Î²-adrenoceptor blockers, 1,3,4-thiadiazole, Schiff base